ANALISIS VEKTOR PADA ALAT PENGUKUR DAN PEMBATAS (APP) 3 PHASA DI PLN UP3 MOJOKERTO - Trisno Sanyoto; Muhammad Septian Wijaya; Zainul Bachtiar Sadoni (CV. Denasya Smart Publisher, 2024)
The high level of electrical energy consumption in the UP3 Mojokerto area has become a significant concern for PT PLN (Persero) UP3 Mojokerto, particularly due to the risk of inaccuracies at transaction points (kWh meters) that may lead to increased energy losses. PT PLN (Persero) seeks to prevent measurement errors or misuse of electrical energy at the Metering and Limiting Equipment (Alat Pengukur dan Pembatas/APP), which could result in financial losses for both the utility company and customers. This study aims to minimize such measurement errors and potential irregularities through vector analysis of APP installed on three-phase customers, using a quantitative research approach. The analysis is supported by vector diagrams and instantaneous data obtained from the Automatic Meter Reading (AMR) application. The results indicate that vector analysis combined with AMR data enables PT PLN (Persero) to detect measurement anomalies in APP at an early stage. Consequently, this approach contributes to reducing potential losses and improving fairness and accuracy in energy transactions for both PT PLN (Persero) and its customers.